Robust amphiprotic konjac glucomannan cross-linked chitosan aerogels for efficient water remediation - Mao, Jiajun (2021)
Robust amphiprotic-konjac glucomannan/chitosan (AP-KGM/CS) aerogels were prepared by modification of KGM with carboxymethyl and quaternary ammonium groups, and then cross-linked with chitosan. The adsorption performance of AP-KGM/CS aerogels on the anionic dyes everacid Orange N-G (C.I. Acid Orange O56), cationic dyes methylene blue (MB) and heavy metal ions (Pb2+, Cu2+, Cd2+) was investigated. The open porous structure of the aerogel has a significant effect on maintaining the structural stability of aerogel and promoting the diffusion and transfer of pollutants to ensure adequate contact between pollutants and adsorption sites. The adsorption equilibrium of anionic dye O56 and cationic dye MB was reached within 300 min, and the saturated adsorption capacities were 267 mg/g and 348 mg/g, respectively. Besides, the adsorption equilibrium of single metal ions Pb2+, Cu2+, and Cd2+ was reached within 120 min, and their saturated adsorption capacities were 469 mg/g, 254 mg/g and 144 mg/g, respectively. Moreover, under the competitive adsorption of three heavy metal ions, the equilibrium adsorption time of Pb2+, Cu2+, and Cd2+ in the mixed solutions (each with a concentration of 600 mg/L) was 240 min, 150 min and 70 min, respectively, and their saturated adsorption capacities were 318 mg/g, 184 mg/g and 94 mg/g, respectively.